Weak compatibility and fixed point theorems for four self-maps in D-metric spaces - Bijendra Singh; Shobha Jain (International Journal of Mathematics and Mathematical Sciences)
This paper establishes one common coincident point theorem and three unique common fixed point theorems for four self-maps in D-metric spaces, which improve and generalize, significantly, the results of Dhage et al. (2003), Dhage (1999), and Rhoades (2003) under weaker assumption using a more general contractive condition. An example, in support of these theorems, has also been constructed. All the results of this paper are new.